PENERAPAN AUDIT INDEPENDEN DAN POLA PEMBINAAN PADA BKM UNTUK MENGEFEKTIFKAN PELAKSANAAN PNPM MANDIRI PERKOTAAN DI KOTA BANDUNG - Luh Gede Maya Untari Wiwaha (LPPM POLITEKNIK LP3I BANDUNG, 2016)
National Program for Community Empowerment or PNPM Urban MP is the realization of government policy that seeks to reduce poverty and ultimately creating a civil society. But so far there are still obstacles in the implementation of the program, including the issue of performance accountability Community Self-reliance Agency (BKM). The research problem is formulated as follows: 1) how BKM response to the presence of an independent auditor?, 2) how the implementation of an independent audit based on the pattern of development in Bandung BKM?, 3) whether the application of the independent audit based development patterns can improve the accountability in the performance of BKM Bandung district?, 4) how the implementation of PNPM MP in Bandung district?, 5) whether an independent audit based on the coaching pattern can streamline BKM PNPM MP in Bandung district?. The study was conducted with the purpose: want to know and analyze the response to the presence of an independent auditor BKM, application independent audit based on the pattern of development in Bandung BKM and answer patterns in the formation of an independent audit is conducted to improve the accountability of performance BKM in Bandung. And determine and analyze the implementation of PNPM MP in Bandung and independent audit based on the coaching pattern can streamline BKM whether PNPM MP in Bandung. The research method uses a descriptive qualitative design of the data collection and in-depth interviews gradual (in-depth interviews), observation and documentation. It is therefore necessary to create a positive assumption of the existence of the auditor is working pattern of an audit. Here the role of the independent auditor who can be expected to change the negative assumptions, because the independent auditor is not bound by government intervention. The task of the independent auditors should not only look for finding problems, but also there is a mission coaching so BKM know how to properly make a true report according to standard. Pattern formation is conducted by an independent auditor aims not only to provide knowledge and understanding of that report generation accountable according to the standard, but it is expected to provide intrinsic motivation so that future auditing of BKM has awareness for its own performance. Performance accountable BKM will have an impact on the effectiveness of the implementation of PNPM MP. Study to improve performance accountability system that BKM MP PNPM actors in implementing PNPM MP.